The Relationship between the Implementation of Clean and Healthy Living Behavior (PHBS) in the Household Environment and the Incidence of Malnutrition in Toddlers in the Batunadua Health Center Working Area - Muhammad Riswal; Anto J. Hadi; Asdi Lastari; Saskiyanto Manggabarani; Syamsopyan Ishak; Nayodi Permayasa (Science Publication: Journal of Public Health and Nutrition, 2026)
ABSTRACT Malnutrition in toddlers is still a significant public health problem at the global and national levels. This study aims to analyze the relationship between the implementation of clean and healthy living behaviors (PHBS) in the household environment and the incidence of malnutrition in toddlers in the working area of the Batunadua Health Center. Methods: This study used an analytical quantitative design with a cross sectional study approach. The population and sample are all toddlers registered in the Batunadua Health Center area. Data were collected using questionnaires and weight measurements of toddlers based on the BB/U index. Data analysis was conducted using the chi-square test with a significance level of α = 0.05. There was a relationship between the history of exclusive breastfeeding and the incidence of malnutrition (p=0.001), there was a relationship between diet and the incidence of malnutrition (p=0.018). There was no association between immunization history (p=0.128) and handwashing habit with soap (p=0.072) with the incidence of malnutrition in toddlers. It was found that exclusive breastfeeding and diet were significantly related to the incidence of malnutrition in toddlers. Immunization and soap hand washing habits did not show a significant relationship in this study. So it is necessary to increase nutritional literacy for families under five. Keywords: PHBS; malnutrition; news; exclusive breast milk; diet.